2016
DOI: 10.7554/elife.16246
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency stimulation-induced peptide release synchronizes arcuate kisspeptin neurons and excites GnRH neurons

Abstract: Kisspeptin (Kiss1) and neurokinin B (NKB) neurocircuits are essential for pubertal development and fertility. Kisspeptin neurons in the hypothalamic arcuate nucleus (Kiss1ARH) co-express Kiss1, NKB, dynorphin and glutamate and are postulated to provide an episodic, excitatory drive to gonadotropin-releasing hormone 1 (GnRH) neurons, the synaptic mechanisms of which are unknown. We characterized the cellular basis for synchronized Kiss1ARH neuronal activity using optogenetics, whole-cell electrophysiology, mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
263
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(282 citation statements)
references
References 66 publications
17
263
1
1
Order By: Relevance
“…Previous work demonstrated that both hM3Dq-and ChR2-mediated stimulation can evoke immediate early Fos expression in AgRP neurons (28,44). However, we have shown that specific frequencies of laser stimulation can modulate the differential release of peptide vs. fast transmitter from ChR2-expressing neurons (6). The more quantitative approach of activating AgRP neurons with ChR2 is not practical for the long periods of time needed to study fertility.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Previous work demonstrated that both hM3Dq-and ChR2-mediated stimulation can evoke immediate early Fos expression in AgRP neurons (28,44). However, we have shown that specific frequencies of laser stimulation can modulate the differential release of peptide vs. fast transmitter from ChR2-expressing neurons (6). The more quantitative approach of activating AgRP neurons with ChR2 is not practical for the long periods of time needed to study fertility.…”
Section: Discussionmentioning
confidence: 63%
“…Thus, neurophysiological mechanisms detect deficits in energy reserves and inhibit the neuroendocrine axis to prevent pregnancy (2,31 (6), and this circuit is likely responsible for attenuating fertility during metabolic deficiency. There may be additional sources of inhibition onto Kiss1 neurons during starvation, but the observation that ablation of AgRP neurons can restore fertility in leptin-deficient mice (15) argues that AgRP neurons are an important source of inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the two kisspeptin neuron populations that innervate GnRH neurons, particular attention has focused upon the arcuate nucleus kisspeptin (ARN KISS ) neurons in terms of pulse generation (14,15). Investigators have shown that ARN KISS neurons coexpress a variety of different neurotransmitters, including glutamate, neurokinin B, and dynorphin (15,16), for which these cells also express functional receptors (17,18). Alongside anatomical evidence, it has been suggested that the ARN KISS neurons may exhibit synchronized behavior that could intermittently activate GnRH neurons and, thus, act as a pulse generator (15,16,19).…”
mentioning
confidence: 99%